Longitudinal outcomes with cancer multigene panel testing in previously tested BRCA1/2 negative patients. Issue 4 (11th March 2020) - Bradbury, Angela R.; Egleston, Brian L.; Patrick‐Miller, Linda J.; Rustgi, Neil; Brandt, Amanda; Brower, Jamie; DiGiovanni, Laura; Fetzer, Dominique; Berkelbach, Christopher; Long, Jessica M.; Powers, Jacquelyn; Stopfer, Jill E.; et al.
Abstract: Although multigene panel testing (MGPT) is increasingly utilized in clinical practice, there remain limited data on patient‐reported outcomes. BRCA 1/2 negative patients were contacted and offered MGPT. Patients completed pre‐ and posttest counseling, and surveys assessing cognitive, affective and behavioral outcomes at baseline, postdisclosure and 6 and 12 months. Of 317 eligible BRCA1/2 negative patients who discussed the study with research staff, 249 (79%) enrolled. Decliners were more likely to be older, non‐White, and recruited by mail or email. Ninety‐five percent of enrolled patients proceeded with MGPT. There were no significant changes in anxiety, depression, cancer specific distress or uncertainty postdisclosure. There were significant but small increases in knowledge, cancer‐specific distress and depression at 6‐12 months. Uncertainty declined over time. Those with a VUS had significant decreases in uncertainty but also small increases in cancer specific distress at 6 and 12 months. Among those with a positive result, medical management recommendations changed in 26% of cases and 2.6% of all tested. Most BRCA1/2 negative patients have favorable psychosocial outcomes after receipt of MGPT results, although small increases in depression and cancer‐specific worry may exist and may vary by result. Medical management changed in few patients. Abstract :